Efektifitas pemberian kompos Trichoderma sp terhadap pertumbuhan dan hasil rumput Setaria (Setaria spachelata) - Maria Erviana Kusuma (JURNAL ILMU HEWANI TROPIKA (JOURNAL OF TROPICAL ANIMAL SCIENCE), 2016)
This study aimed was to know the effect of Trichoderma sp compost on the growth and production of Setaria grass (Setaria spachelata) and to know the dosage of Trichoderma sp compost that giving the best result to the growth and production of Setaria grass. This research was designed by using Completely Random Design (CRD) with single factor experiment that was the dosage of Trichoderma sp compost : 0 ton ha-1, 10 ton ha-1, 20 ton ha-1 , 30 ton ha-1 and 40 ton ha-1. The result showed that the applications of Trichoderma sp compost giving the effect to the number of tillers (4, 6, 8 week after planting), the crop height in 6 and 8 week after planting and the crop wet weight. The giving of Trichoderma sp compost 30 ton ha-1 and 40 ton ha-1 resulted the same effect on Setaria grass wet weight. Key words : Effectiveness, compost, Trichoderma sp